2018
DOI: 10.24926/iip.v9i2.971
|View full text |Cite
|
Sign up to set email alerts
|

Drug Therapy Problem Identification and Resolution by Clinical Pharmacists in a Family Medicine Residency Clinic

Abstract: Purpose: There are limited data to evaluate the impact of ambulatory clinical pharmacist recommendations on family medicine resident prescribing and monitoring of medications. The purpose of this study is to begin to gain insight in this area by answering the research question, “How many ambulatory clinical pharmacist recommendations for drug therapy problem (DTP) resolution are implemented on the day of a medication therapy management (MTM) visit in an outpatient family medicine residency clinic?” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“… 14 , 17 , 18 Hence, identifying risk factors, timely medication therapy review and taking correction measures for identified DRPs are important to reduce the harmful outcomes of DRPs. 19 22 Data about the prevalence of DRPs in a healthcare system would be useful to plan and implement strategies to reduce the incidence and resolve a DRP before it harms the patient. Hence, this systematic review and meta-analysis was undertaken with the aim of quantifying the prevalence of DRPs and identifying commonly encountered types of DRPs in Ethiopian healthcare settings.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 17 , 18 Hence, identifying risk factors, timely medication therapy review and taking correction measures for identified DRPs are important to reduce the harmful outcomes of DRPs. 19 22 Data about the prevalence of DRPs in a healthcare system would be useful to plan and implement strategies to reduce the incidence and resolve a DRP before it harms the patient. Hence, this systematic review and meta-analysis was undertaken with the aim of quantifying the prevalence of DRPs and identifying commonly encountered types of DRPs in Ethiopian healthcare settings.…”
Section: Introductionmentioning
confidence: 99%
“…In 32 of the quantitative studies, PI actions were not detailed. PIs were not described in the descriptive and retrospective studies [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Other sources only focused on the impacts or level of acceptance of PIs or just show general results of the service [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…This observation contradicts other findings that show poor outcomes when multiple drugs are used. 23 Refractoriness to the medication negatively affected social relations domains while drug interaction reduced psychological and overall HRQoL scores. This portrayed that the personal relationships deteriorated due to the stress of treatment not attaining the desired result.…”
Section: Discussionmentioning
confidence: 99%